Copolymers based on epoxidized soy bean oil and diglycidyl ether of bisphenol a: Relation between morphology and fracture behavior. Issue 3 (10th May 2013) - Altuna, Facundo I.; Pettarin, Valeria; Martin, Loli; Retegi, Aloña; Mondragon, Iñaki; Ruseckaite, Roxana A.; Stefani, Pablo M.
<x xml:space="preserve">Abstract</x> Epoxidized soybean oil (ESO) was proved to be a good alternative to partially replace a synthetic commercial epoxy resin in a formulation to obtain thermosetting polymer, contributing to transform a vegetable oil into a higher added value product. This work focuses on the study of the fracture behavior of copolymers based on anhydride‐cured epoxy systems with different contents of ESO as a replacement for the synthetic resin. It was found that fracture toughness was greatly improved when replacing diglycidyl ether of bisphenol A (DGEBA) by ESO, being the critical stress intensity factor (KIC) 1.067 MPa·m1/2 for cured ESO and 0.557 MPa·m1/2 for cured DGEBA. The better performance of ESO networks was ascribed to its higher ability to attain plastic deformation. Moreover, for DGEBA‐ESO systems, the morphologies generated during the curing process were also considered to account for the observed results. POLYM. ENG. SCI., 54:569–578, 2014. © 2013 Society of Plastics Engineers